Pharmacokinetics and ex vivo pharmacodynamics of Minocycline against Salmonella abortus equi in donkey plasma and tissue cage fluid. (March 2021) - Li, Zaijian; Liu, Wenqiang; Su, Jianqing; Chu, Xiuling; Wang, Changfa
Abstract: Tissue Cage (TC) model was used to evaluate the pharmacokinetics and ex vivo pharmacodynamics of Minocycline (MINO) after intramuscular (IM) administration to donkeys at 4 mg/kg body-weight. The Cmax of MINO with 1.79 and 2.63 μg mL −1 was obtained at 2.96 and 1.41 h in TCF (tissue cage fluid) and plasma respectively. The absorption half-lives (t1/2ka ) of MINO were calculated to be 0.71 h in TCF and 0.32 h in plasma, whereas the elimination half-lives (t1/2ke ) were 10.46 h in TCF and 5.95 h in plasma. The distribution volume (Vd /F) of MINO was estimated to be 1.84 L kg −1 in TCF and 1.28 L kg −1 in plasma. The total clearance (CLb /F) of MINO was computed as 0.12 and 0.15 L/ (h·kg) in TCF and plasma respectively. The area under the concentration-time curve (AUC) of MINO was 32.77 μg mL −1 h in TCF and 25.27 μg mL −1 h in plasma, respectively.The ex vivo time-kill curves were established for plasma and TCF samples using Salmonella abortus equi . The MIC and MBC of MINO against salmonella were 0.08 and 0.16 μg mL −1 for plasma, 0.04 and 0.08 μg mL −1 for TCF. The plasma Cmax /MIC and AUC/MIC values after IM administration were 32.88 ± 9.87 and 315.88 ± 42.65 h, respectively. The TCF Cmax /MIC and AUC/MIC values after IM administration were 44.75 ± 9.32 and 819.25 ± 65.23 h, respectively. The values of T > MIC were approximately >36 h in plasma and > 65 h in TCF. These findings from this study suggest that MINO may be therapeutically effective in diseases of donkeys caused by salmonella when used at a dose of 4 mg/kg IM administration. Highlights: This study has demonstrated that MINO concentration exceeded the MIC for up to 24 h in plasma and 65 h in TCF. The results suggested that MINO may prove to be therapeutically successful in treating infectious disease of donkey Time-dependent characteristics needs to be confirmed in vivo PK/PD model and fractionation schedules. These in vitro models will provide practical data that are much closer to the in vivo situation.